Pengaruh Pengetahuan Gizi, Sikap Ibu dan Asupan Zat Gizi Makro terhadap Status Gizi Anak di SDN Gedangrowo Prambon Sidoarjo : Hubungan Pengetahuan Gizi, Sikap Ibu dan Asupan Zat Gizi Makro dengan Status Gizi Anak di SDN Gedangrowo Prambon Sidoarjo - Hilda Kristia Margareta; Veni Indrawati; Siti Sulandjari (Amerta Nutrition, 2023)
Background: A mother's nutritional knowledge, attitude, and children’s macronutrient intake can affect the nutritional status of elementary school-age children. Objectives: This research analyzes the relationship between a mother’s nutritional knowledge, attitude, children’s macronutrient intake, and children’s nutritional status at SDN Gedangrowo Prambon Sidoarjo. Methods: This research used a quantitative approach with a cross-sectional research design. It involved 110 students as research participants. The data were collected using multiple instruments. The research used the mother's nutritional knowledge test sheet to see the mother's nutritional knowledge knowledge. While an attitude questionnaire was distributed to investigate mothers' attitudes, the intake of macronutrients was measured using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). These data were then analyzed using Logistic Regression Analysis. Results: The results showed that mothers’ nutritional knowledge (p=0.002), attitude (p=0.002), children’s energy intake (p=0.001), protein intake (p=0.000) and carbohydrate intake (p=0.008) had a relationship with children's nutritional status. Nevertheless, no relationship was found between fat intake (P=0,067) and children's nutritional status. The nutritional status of children is divided into undernutrition, good nutrition, and overnutrition. Conclusions: Mother nutritional knowledge, attitude, and children’s energy, protein, and carbohydrate intake are related to children's nutritional status. There is no relationship between fat intake and children's nutritional status. Based on multivariate analysis, it is reported that protein intake has a strong relationship with children's nutritional status.